Dynamic two-dimensional organosilicon polymer and preparation method and application thereof

By introducing dynamic two-dimensional structures and reversible covalent bonds into silicone materials, the shortcomings in existing silicone materials in terms of service life and recycling are solved, and the performance improvement of high-performance electrolyte membranes and batteries is achieved.

CN119591819AActive Publication Date: 2025-03-11SHANDONG UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510138527.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-11
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing silicone materials are produced by irreversible covalent bond coupling, resulting in insufficient product service life and recycling.

Method used

A dynamic two-dimensional silicone polymer is provided, with structural units having reversible covalent bonds (C=N bonds), prepared by specific synthetic methods, including reaction of 2-(4-bromophenyl)-1,3-dioxolane with dichlorosilane, deprotection and polymerization with melamine.

Benefits of technology

The conductivity, mechanical properties and cycle stability of the electrolyte membrane are improved, thereby improving the performance and service life of the battery, while improving the recycling of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591819A_ABST
    Figure CN119591819A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic silicon materials, in particular to a dynamic two-dimensional organic silicon polymer as well as a preparation method and application thereof. The dynamic two-dimensional organosilicon polymer provided by the invention has a reversible covalent bond (C = N bond), and compared with irreversible covalent bond organosilicon, the dynamic two-dimensional organosilicon polymer can improve the cyclic utilization of a material while ensuring the performance and stability of the material; the dynamic two-dimensional organosilicon polymer provided by the invention combines the structural advantages of a polymer and a two-dimensional nano material, and realizes efficient in-plane charge and energy transfer while ensuring the mechanical properties of the material. When the dynamic two-dimensional organosilicon polymer provided by the invention is used for preparing an electrolyte membrane, the conductivity, the mechanical property and the cycling stability of the electrolyte membrane can be improved, so that the performance of a battery is improved, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organosilicon materials, and in particular to a dynamic two-dimensional organosilicon polymer and a preparation method and application thereof. Background Art

[0002] Since the first organosilicon compound was synthesized in 1863, organosilicon materials have been widely used in aerospace, electronics, energy and other fields. Organosilicon materials are usually formed by covalent bonds such as Si-Si, Si-C, Si-OC, etc., and have excellent properties such as high and low temperature resistance, aging resistance, and biological inertness. Currently, most commonly used organosilicon materials are generated by non-reversible covalent bond coupling and have a linear structure. There is room for further improvement in product life and recyclability. Summary of the invention

[0003] The object of the present invention is to provide a dynamic two-dimensional organosilicon polymer and a preparation method and application thereof. The dynamic two-dimensional organosilicon polymer provided by the present invention is used to prepare an electrolyte membrane, which can improve the electrical conductivity, mechanical properties and cycle stability of the electrolyte membrane, thereby improving the performance and service life of the battery.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a dynamic two-dimensional organosilicon polymer, characterized in that the structural unit has a structure shown in Formula 1: Formula 1; In Formula 1, R is -CH3, -C2H5, -C3H7, -CH(CH3)2, -C6H6 or -O-[Si(CH3)2-O] n -CH3, n is an integer from 1 to 11.

[0005] The present invention provides a method for preparing the dynamic two-dimensional organosilicon polymer described in the above scheme, comprising the following steps: (1) dissolving 2-(4-bromophenyl)-1,3-dioxolane in tetrahydrofuran and cooling to -60 to -95°C, adding an organic lithium reagent to carry out an intermediate reaction, adding a tetrahydrofuran solution of dichlorosilane to the obtained intermediate system and heating to room temperature to carry out a nucleophilic substitution reaction to obtain a compound with a structure shown in Formula 3; The dichlorosilane has a structure shown in Formula 2: Formula 2; Formula 3; In Formula 2 and Formula 3, R is -CH3, -C2H5, -C3H7, -CH(CH3)2, -C6H6 or -O-[Si(CH3)2-O] n -CH3, n is an integer from 1 to 11; (2) dissolving the compound of the structure represented by Formula 3 in acetone and mixing the mixture with water and a strong inorganic acid to carry out a deprotection reaction to obtain a compound of the structure represented by Formula 4; Formula 4; (3) The compound having the structure shown in Formula 4 is polymerized with melamine to obtain the dynamic two-dimensional organosilicon polymer.

[0006] Preferably, in step (1), the molar ratio of 2-(4-bromophenyl)-1,3-dioxolane to dichlorosilane is (1-4):1.

[0007] Preferably, in step (1), the molar ratio of the 2-(4-bromophenyl)-1,3-dioxolane to the organic lithium reagent is 1:(0.5-1.5); The organic lithium reagent includes one or more of n-butyl lithium, sec-butyl lithium and tert-butyl lithium.

[0008] Preferably, in step (2), the mass ratio of the compound having the structure represented by formula 3 to the volume ratio of water is 1 g: 8-12 mL.

[0009] Preferably, in step (3), the polymerization reaction of the compound represented by formula 4 with melamine comprises method 1 or method 2; The method 1 comprises the following steps: The compound of the structure shown in Formula 4 and melamine are dissolved in a mixed solvent, an organic weak acid catalyst is added to the obtained solution, and then the solution is vacuum-sealed and allowed to stand under vacuum-sealed conditions to perform a polymerization reaction; the mixed solvent is a combination of 1,4-dioxane and mesitylene, or a combination of n-butanol and o-dichlorobenzene; The second method comprises the following steps: The compound with the structure shown in Formula 4 and melamine are dissolved in a high boiling point solvent, an organic weak acid catalyst is added to the obtained solution, and a polymerization reaction is carried out in an inert atmosphere or a vacuum atmosphere under static conditions; the high boiling point solvent includes one or more of dimethyl sulfoxide, chlorobenzene, dichlorobenzene and N,N-dimethylformamide.

[0010] Preferably, when the polymerization reaction is carried out using method 1 or method 2, the molar ratio of the compound of the structure represented by formula 4 to melamine is 3:(1.8-2.2).

[0011] Preferably, when the polymerization reaction is carried out by method 1, the polymerization reaction temperature is 60-80° C. and the time is 60-80 h; When the polymerization reaction is carried out using method 2, the polymerization reaction temperature is 110-130° C. and the time is 60-80 hours.

[0012] The present invention provides the application of the dynamic two-dimensional organosilicon polymer described in the above scheme or the dynamic two-dimensional organosilicon polymer prepared by the preparation method described in the above scheme in an electrolyte membrane.

[0013] Preferably, the electrolyte membrane comprises a matrix, an electrolyte salt and a dynamic two-dimensional organosilicon polymer, and the mass of the dynamic two-dimensional organosilicon polymer is 1-5% of the mass of the matrix.

[0014] The dynamic two-dimensional organosilicon polymer provided by the present invention has a reversible covalent bond (C=N bond). Compared with non-reversible covalent bond organosilicon, it can improve the recycling of materials while ensuring the performance and stability of the materials; the dynamic two-dimensional organosilicon polymer provided by the present invention combines the structural advantages of polymers and two-dimensional nanomaterials, and achieves efficient in-plane charge and energy transfer while ensuring the mechanical properties of the materials. The dynamic two-dimensional organosilicon polymer provided by the present invention is used to prepare an electrolyte membrane, which can improve the conductivity, mechanical properties and cycle stability of the electrolyte membrane, thereby improving the performance and service life of the battery.

[0015] The dynamic two-dimensional organosilicon polymer provided by the present invention is a brand-new structure, which will foreseeably bring novel changes to the field of traditional organosilicon materials and inject new vitality. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The hydrogen spectrum (a) and carbon spectrum (b) of 2-(4-bromophenyl)-1,3-dioxolane; Figure 2 The hydrogen spectrum (a) and carbon spectrum (b) of bis(4-(1,3-dioxolan-2-yl)phenyl)dimethylsilane; Figure 3 The hydrogen spectrum (a) and carbon spectrum (b) of 4,4'-(dimethylsilanediyl)benzaldehyde; Figure 4 The XPS spectrum of the dynamic two-dimensional organosilicon polymer prepared in Example 1; Figure 5 This is the C 1s-XPS spectrum of the dynamic two-dimensional organosilicon polymer prepared in Example 1; Figure 6 This is the N-XPS spectrum of the dynamic two-dimensional organosilicon polymer prepared in Example 1; Figure 7 This is the Si-XPS spectrum of the dynamic two-dimensional organosilicon polymer prepared in Example 1; Figure 8 The infrared spectra of 4,4'-(dimethylsilanediyl)benzaldehyde, melamine, and 2D-COSi-Me prepared in Example 1 and Example 2; Fig. 9 This is the thermogravimetric analysis diagram of melamine; Fig.10 This is a thermogravimetric analysis diagram of the dynamic two-dimensional organosilicon polymer of Example 1; Fig.11 is an optical microscope photograph of the dynamic two-dimensional organosilicon polymer of Example 1, a~d are different particles; Fig.12 TEM images (a and b) and HRTEM images (c and d) of the dynamic two-dimensional organosilicon polymer of Example 1; Fig.13 This is a physical photo of the electrolyte slurry; Fig.14 This is a photo of the electrolyte membrane doped with 1% 2D-COSi-Me; Fig.15 SEM photos of PEO electrolyte membrane, where a~c are surface photos and d is a cross-sectional photo; Fig.16 SEM photos of the electrolyte membrane doped with 2% 2D-COSi-Me, where a~c are surface photos and d is a cross-sectional photo; Fig.17 Element analysis diagrams of different positions of the electrolyte membrane doped with 2% 2D-COSi-Me, where b and c are the element analysis results of a, and e and f are the element analysis results of d; Fig.18 Cycling stability test results of batteries assembled with PEO electrolyte membrane (a and c) and electrolyte membrane doped with 1% 2D-COSi-Me (b and d); Fig.19 The stability test results of electrolyte membranes doped with 1% 2D-COSi-Me (a), 1.5% 2D-COSi-Me (b), 2% 2D-COSi-Me (c) and 2.5% 2D-COSi-Me (d); Fig. 20 The electron transfer activation energy (a) and the conductivity comparison diagram in the range of 30~70℃ of the PEO electrolyte membrane and the electrolyte membrane doped with 1% 2D-COSi-Me (b); Fig.21 This is a comparison chart of the stretching results of the PEO electrolyte membrane and the electrolyte membrane doped with 1% 2D-COSi-Me. DETAILED DESCRIPTION

[0017] The present invention provides a dynamic two-dimensional organosilicon polymer, wherein the structural unit has a structure shown in Formula 1: Formula 1; In Formula 1, R is -CH3, -C2H5, -C3H7, -CH(CH3)2, -C6H6, or -O-[Si(CH3)2-O] n -CH3, n is an integer from 1 to 11.

[0018] In the present invention, the wavy lines in Formula 1 represent connecting the same structural units.

[0019] The dynamic two-dimensional organosilicon polymer provided by the present invention has a reversible covalent bond (C=N bond). Compared with non-reversible covalent bond organosilicon, it can improve the recycling of materials while ensuring the performance and stability of the materials; the dynamic two-dimensional organosilicon polymer provided by the present invention combines the structural advantages of polymers and two-dimensional nanomaterials, and achieves efficient in-plane charge and energy transfer while ensuring the mechanical properties of the materials. The dynamic two-dimensional organosilicon polymer provided by the present invention is used to prepare an electrolyte membrane, which can improve the conductivity, mechanical properties and cycle stability of the electrolyte membrane, thereby improving the performance and service life of the battery.

[0020] The dynamic two-dimensional organosilicon polymer provided by the present invention is a brand-new structure, which will foreseeably bring novel changes to the field of traditional organosilicon materials and inject new vitality.

[0021] The present invention provides a method for preparing the dynamic two-dimensional organosilicon polymer described in the above scheme, comprising the following steps: (1) dissolving 2-(4-bromophenyl)-1,3-dioxolane in tetrahydrofuran and cooling to -60 to -95°C, adding an organic lithium reagent to carry out an intermediate reaction, adding a tetrahydrofuran solution of dichlorosilane to the obtained intermediate system and heating to room temperature to carry out a nucleophilic substitution reaction to obtain a compound with a structure shown in Formula 3; The dichlorosilane has a structure shown in Formula 2: Formula 2; Formula 3; In Formula 2 and Formula 3, R is -CH3, -C2H5, -C3H7, -CH(CH3)2, -C6H6 or -O-[Si(CH3)2-O] n -CH3, n is an integer from 1 to 11; (2) dissolving the compound of the structure represented by Formula 3 in acetone and mixing the mixture with water and a strong inorganic acid to carry out a deprotection reaction to obtain a compound of the structure represented by Formula 4; Formula 4; (3) The compound having the structure shown in Formula 4 is polymerized with melamine to obtain the dynamic two-dimensional organosilicon polymer.

[0022] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.

[0023] The present invention dissolves 2-(4-bromophenyl)-1,3-dioxolane in tetrahydrofuran and then cools the mixture to -60 to -95°C, adds an organic lithium reagent to carry out an intermediate reaction, adds a tetrahydrofuran solution of dichlorosilane to the obtained intermediate system, and heats the mixture to room temperature to carry out a nucleophilic substitution reaction, thereby obtaining a compound with a structure shown in Formula 3.

[0024] In the present invention, the 2-(4-bromophenyl)-1,3-dioxolane can be commercially available or prepared by methods well known in the art. In a specific embodiment of the present invention, the 2-(4-bromophenyl)-1,3-dioxolane is prepared in-house, and the preparation method is as follows: 4-bromobenzaldehyde (15.00 g, 81 mmol) is added to a two-necked flask, anhydrous toluene (90 mL) is added to dissolve, and then ethylene glycol (7.50 g, 6.74 mL, 120.8 mmol) and p-toluenesulfonic acid (66 mg, 0.35 mmol) are added. After heating and reflux at 145°C under N2 conditions for 24 h, it is washed with saturated NaHCO3 solution and brine, and the organic layer is dried with MgSO4, filtered, and rotary evaporated to obtain a crude product, and the 2-(4-bromophenyl)-1,3-dioxolane pure product is obtained by vacuum distillation (set at 135°C, the thermometer shows 106°C).

[0025] In the present invention, the structural formula of the 2-(4-bromophenyl)-1,3-dioxolane is as shown in Formula 5: Formula 5.

[0026] In the present invention, tetrahydrofuran is used as a solvent, and the mass ratio of the 2-(4-bromophenyl)-1,3-dioxolane to the volume ratio of tetrahydrofuran is preferably 1 g: (8-13) mL, more preferably 1 g: (9-11) mL. The present invention has no special requirements for the dissolution temperature, as long as the 2-(4-bromophenyl)-1,3-dioxolane can be completely dissolved.

[0027] In the present invention, the 2-(4-bromophenyl)-1,3-dioxolane is dissolved in tetrahydrofuran and then cooled to -60 to -95°C. In specific embodiments, the temperature can be cooled to -60°C, -70°C, -78°C, -85°C, -90°C or -95°C, which are not listed here.

[0028] In the present invention, the organolithium reagent preferably includes one or more of n-butyl lithium, sec-butyl lithium and tert-butyl lithium; the molar ratio of the 2-(4-bromophenyl)-1,3-dioxolane to the organolithium reagent is preferably 1:(0.5-1.5), more preferably 1:(0.8-1.2), and further preferably 1:1. In the present invention, the organolithium reagent is preferably added dropwise.

[0029] In the present invention, the intermediate reaction is preferably carried out under stirring conditions, and the intermediate reaction time is preferably 1 hour. In the intermediate reaction process of the present invention, the lithium in the organolithium reagent can replace the bromine atom in 2-(4-bromophenyl)-1,3-dioxolane to generate a phenyllithium intermediate product, and then further undergoes a nucleophilic substitution reaction with the subsequently added dichlorosilane.

[0030] In the present invention, the organic lithium is highly active and generates heat when reacting with 2-(4-bromophenyl)-1,3-dioxolane. The present invention reduces the temperature to -60 to -95°C for the reaction, which can prevent other side reactions.

[0031] In the present invention, the dichlorosilane has a structure shown in Formula 2: Formula 2.

[0032] In the present invention, the concentration of the tetrahydrofuran solution of dichlorosilane is preferably 0.5-2 mol / L. In the present invention, the tetrahydrofuran solution of dichlorosilane is preferably added dropwise.

[0033] In the present invention, the temperature increase is preferably natural temperature increase.

[0034] In the present invention, the nucleophilic substitution reaction is preferably carried out under stirring conditions, and the time of the nucleophilic substitution reaction is preferably 0.5 to 1.5 h, more preferably 1 h.

[0035] In the present invention, after the nucleophilic substitution reaction time is reached, methanol is preferably added to the reaction system to quench the reaction, and then the obtained product is poured into a saturated NaHCO3 solution, the organic layer is separated, and then extracted three times with dichloromethane, dried with MgSO4, filtered, and rotary evaporated to obtain a compound with a structure shown in Formula 3; Formula 3.

[0036] In the present invention, taking n-butyl lithium as an example, the reaction equation for preparing the compound of the structure shown in Formula 3 is shown in Formula (1): Formula (1).

[0037] After obtaining the compound of the structure shown in Formula 3, the present invention dissolves the compound of the structure shown in Formula 3 in acetone and then mixes it with water and a strong inorganic acid to perform a deprotection reaction to obtain a compound of the structure shown in Formula 4.

[0038] In the present invention, the mass ratio of the compound of the structure represented by Formula 3 to the volume ratio of acetone is preferably 1 g: (10-40) mL, more preferably 1 g: (20-30) mL. The acetone is used as a solvent.

[0039] In the present invention, the mass ratio of the compound of the structure represented by Formula 3 to the volume ratio of water is preferably 1 g: 8-12 mL, more preferably 1 g: 10 mL. The water is used as a reactant.

[0040] In the present invention, the inorganic strong acid is preferably p-toluenesulfonic acid or dilute sulfuric acid; the mass ratio of the compound of the structure shown in Formula 3 to the inorganic strong acid is preferably (15-15.5):1, and in a specific embodiment of the present invention, the mass ratio of the compound of the structure shown in Formula 3 to the inorganic strong acid is 15.15:1. In the present invention, the inorganic strong acid is used as a catalyst for the reaction.

[0041] In the present invention, the deprotection is preferably carried out under reflux conditions, and the reflux temperature is preferably 50-80°C. In a specific embodiment, the reflux temperature may be 50°C, 60°C, 70°C or 80°C. In the present invention, the deprotection reaction equation is shown in the following formula (2): Formula (2).

[0042] After the deprotection reaction is completed, the present invention cools the obtained reaction liquid to room temperature, adds the cooled liquid to a saturated NaHCO3 solution, extracts with dichloromethane, MgSO4 is dried, filtered, and then distilled under reduced pressure to obtain a compound with a structure shown in Formula 4; Formula 4.

[0043] After obtaining the compound with the structure shown in Formula 4, the present invention conducts a polymerization reaction between the compound with the structure shown in Formula 4 and melamine to obtain the dynamic two-dimensional organosilicon polymer.

[0044] The present invention preferably adopts method 1 or method 2 to polymerize the compound having the structure represented by formula 4 with melamine.

[0045] The following first describes method one.

[0046] In the present invention, the method 1 preferably comprises the following steps: dissolving the compound of the structure shown in Formula 4 and melamine in a mixed solvent, adding an organic weak acid catalyst to the obtained solution and then vacuum sealing it, and performing a polymerization reaction under vacuum sealing and static conditions.

[0047] In the present invention, the mixed solvent is preferably a combination of 1,4-dioxane and mesitylene, or a combination of n-butanol and o-dichlorobenzene. When 1,4-dioxane and mesitylene are combined, the volume ratio of 1,4-dioxane and mesitylene is preferably 4:1; when n-butanol and o-dichlorobenzene are combined, the volume ratio of n-butanol and o-dichlorobenzene is preferably 5:1.

[0048] In the present invention, the molar ratio of the compound of the structure represented by Formula 4 to melamine is preferably 3:(1.8-2.2), more preferably 3:2; the mass ratio of melamine to the mixed solvent is preferably 7:(6000-7000), more preferably 7:6600.

[0049] In the present invention, the dissolution is preferably carried out at 70°C.

[0050] In the present invention, the organic weak acid catalyst preferably includes one or more of formic acid, acetic acid, trifluoroacetic acid and propionic acid; the concentration of the formic acid is preferably 6M; and the mass ratio of the organic weak acid catalyst to melamine is preferably 3:1.

[0051] In the present invention, the vacuum is preferably drawn to -60 to -80 kPa.

[0052] In the present invention, the polymerization reaction temperature is preferably 70° C., and the polymerization reaction time is preferably 72 h.

[0053] After the polymerization reaction is completed, the present invention preferably cools the obtained product liquid, then filters it, and washes the filter cake with methanol to obtain the dynamic two-dimensional organosilicon polymer.

[0054] The second method is described below.

[0055] In the present invention, the second method preferably comprises the following steps: dissolving the compound of the structure shown in Formula 4 and melamine in a high boiling point solvent, adding an organic weak acid catalyst to the obtained solution, and performing a polymerization reaction in an inert atmosphere or a vacuum atmosphere and under static conditions.

[0056] In the present invention, the molar ratio of the compound of the structure shown in Formula 4 to melamine is preferably 3: (1.8-2.2), more preferably 3: 2. The dosage ratio of melamine to the high boiling point solvent is preferably 70 mg: (5-7) mL, more preferably 70 mg: 6 mL; the high boiling point solvent preferably includes one or more of dimethyl sulfoxide, chlorobenzene, dichlorobenzene and N, N-dimethylformamide; the type and dosage of the organic acid catalyst are the same as those in method 1, and will not be repeated here.

[0057] In the present invention, the gas providing the inert atmosphere is preferably one or more of nitrogen, helium, neon and argon.

[0058] After adding the organic weak acid catalyst, the present invention preferably performs a freeze-evacuate-thaw-fill inert gas cycle on the obtained reaction system, and seals the reaction system after filling to provide the inert atmosphere required for the polymerization reaction.

[0059] In the present invention, the freezing temperature is preferably -80°C, and the time is preferably 5 minutes; the vacuuming time is preferably 180 seconds; the thawing temperature is preferably room temperature, and the time is preferably 20 minutes; and the inert gas is preferably filled to normal pressure.

[0060] In the present invention, the freezing-evacuation-thawing-inert gas filling is preferably repeated 3 times. The present invention cyclically performs freezing-evacuation-thawing-inert gas filling, and the atmosphere in the reaction system can be replaced with an inert gas.

[0061] In the present invention, the vacuum degree of the vacuum atmosphere is preferably -60 kPa to -80 kPa.

[0062] In the present invention, the polymerization reaction temperature is preferably 110-130°C, and the polymerization reaction time is preferably 60-80h; in a specific embodiment, the polymerization reaction temperature can be 110°C, 120°C or 130°C, and the polymerization reaction time can be 60h, 72h, 76h or 80h.

[0063] After the polymerization reaction is completed, the present invention preferably cools the obtained product liquid and then filters it, and the obtained solid is then washed with tetrahydrofuran and methanol respectively to obtain the dynamic two-dimensional organosilicon polymer.

[0064] In the present invention, although the dynamic two-dimensional organosilicon polymer prepared by the above two methods has been washed, some unreacted melamine still remains. In the present invention, it is preferred to further remove it by solvent extraction.

[0065] The present invention has no special requirements for the solvent extraction process, and a solvent extraction process well known in the art can be used, such as Soxhlet extraction.

[0066] The present invention provides the application of the dynamic two-dimensional organosilicon polymer described in the above scheme or the dynamic two-dimensional organosilicon polymer prepared by the preparation method described in the above scheme in an electrolyte membrane.

[0067] In the present invention, the electrolyte membrane preferably includes a matrix, an electrolyte salt and a dynamic two-dimensional organosilicon polymer; the matrix preferably includes polyethylene oxide; the electrolyte salt preferably includes lithium bis(trifluoromethanesulfonyl imide); the mass of the dynamic two-dimensional organosilicon polymer is preferably 1-5% of the mass of the matrix, and in a specific embodiment, the mass of the dynamic two-dimensional organosilicon polymer can be 1%, 2%, 3%, 4% or 5% of the mass of the matrix.

[0068] The present invention has no special requirements on the preparation process of the electrolyte membrane, and any preparation process known in the art may be used.

[0069] The dynamic two-dimensional organosilicon polymer provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0070] Example 1 A dynamic two-dimensional organosilicon polymer having a structure shown in the synthetic formula 1-1: Formula 1-1.

[0071] The specific steps are as follows: (1) 4-bromobenzaldehyde (15.00 g, 81 mmol) was added to a two-necked flask, and anhydrous toluene (90 mL) was added to dissolve it. Ethylene glycol (7.50 g, 6.74 mL, 120.8 mmol) and p-toluenesulfonic acid (66 mg, 0.35 mmol) were then added. The mixture was heated to reflux at 145°C under N2 for 24 h, and then washed with saturated NaHCO3 solution and brine. The organic layer was dried over MgSO4, filtered, and rotary evaporated to obtain a crude product. The crude product was distilled under reduced pressure (set at 135°C, and the thermometer read 106°C) to obtain pure 2-(4-bromophenyl)-1,3-dioxolane as a white solid.

[0072] 1.83 g of 2-(4-bromophenyl)-1,3-dioxolane was dissolved in 20 mL of tetrahydrofuran (THF), cooled to -78 °C and then 1.6 M n-butyl lithium (5.1 mL, 8.16 mmol) was added dropwise. After stirring for 1 h, a white precipitate was obtained. 2 mL of a THF solution containing 515 mg of dichlorodimethylsilane was added dropwise. After naturally warming to room temperature, the mixture was stirred for 1 h for nucleophilic substitution reaction to obtain a light yellow solution. After quenching the reaction with 1 mL of methanol, the solution was poured into a saturated NaHCO3 solution. After separating the organic layer, the solution was extracted three times with dichloromethane, dried with MgSO4, filtered, and rotary evaporated to obtain bis(4-(1,3-dioxolane-2-yl)phenyl)dimethylsilane (Formula 6); Formula 6.

[0073] (2) Dissolve bis(4-(1,3-dioxolan-2-yl)phenyl)dimethylsilane (1 g, 2.8 mmol) in 30 mL of acetone, add 10 mL of water until slightly turbid, add 66 mg of p-toluenesulfonic acid and heat to 70 °C and reflux for 10 min. After cooling, add 20 mL of saturated NaHCO3 solution, extract with dichloromethane, dry with MgSO4, filter and distill under reduced pressure to obtain 4,4'-(dimethylsilanediyl)benzaldehyde (Formula 7).

[0074] Formula 7.

[0075] (3) Solvothermal conditions: Add melamine (70 mg, 0.56 mmol) and 4,4'-(dimethylsilanediyl)benzaldehyde (240 mg, 0.89 mmol) to a 30 mL hard glass tube and dissolve in 6 mL dimethyl sulfoxide. After adding 0.6 mL of 6 M acetic acid, the mixture was ultrasonically dispersed for 30 min. After three cycles of freeze-evacuation-thaw-inflation, the glass tube was sealed and allowed to react at 120 °C for 3 days. After cooling, the solid was filtered and washed with tetrahydrofuran and methanol respectively to obtain a dynamic two-dimensional organosilicon polymer with the structure shown in Formula 1-1, which was recorded as 2D-COSi-Me (yield 38%).

[0076] Example 2 The only difference from Example 1 is that step (3) is replaced by the following steps: Vacuum conditions: melamine (70 mg, 0.56 mmol) and 4,4'-(dimethylsilanediyl)benzaldehyde (240 mg, 0.89 mmol) were added to a 30 mL hard glass tube and dissolved in 6 mL dimethyl sulfoxide. After adding 0.6 mL of 6 M acetic acid, the mixture was ultrasonically dispersed for 30 min. After three cycles of freezing-evacuation-thawing-inflating, the glass tube was evacuated and sealed, and allowed to react at 120 ° C for 3 days. After cooling, the solid was filtered and washed with tetrahydrofuran and methanol respectively to obtain a dynamic two-dimensional organosilicon polymer, recorded as 2D-COSi-Me (yield 40%).

[0077] Example 3 The only difference from Example 1 is that step (3) is replaced by the following steps: Melamine (0.16 mmol), 4,4'-(dimethylsilanediyl)benzaldehyde (0.24 mmol), 1,4-dioxane (5 mL) and mesitylene (1.25 mL) were added to a 20 mL glass bottle. After heating to 70 °C until the precursor dissolved, 3 mL of acetic acid (10.5 M) was added, and the mixture was sealed after vacuuming. The mixture was heated at 70 °C for 72 h without stirring. After cooling, the mixture was filtered and washed with methanol to obtain a dynamic two-dimensional organosilicon polymer (yield 45%).

[0078] Embodiments 4 to 9 The only difference from Example 1 is that the dichlorodimethylsilane in step (1) is replaced by other dichlorosilanes, and the structural formula is Formula 2. The substituents R in Formula 2 are -C2H5, -C3H7, -CH(CH3)2, -C6H5, -O-Si(CH3)2-O-CH3 and -O-[Si(CH3)2-O] 11-CH3, the R of the obtained dynamic two-dimensional organosilicon polymer with the structure shown in formula 1 is -C2H5, -C3H7, -CH(CH3)2, -C6H5, -O-Si(CH3)2-O-CH3 and -O-[Si(CH3)2-O] 11 -CH3.

[0079] Structural characterization: (1) The 2-(4-bromophenyl)-1,3-dioxolane prepared in Example 1 was tested by hydrogen nuclear magnetic resonance (H-NMR) and carbon nuclear magnetic resonance (C-NMR). The results are as follows: Figure 1 As shown, a is the hydrogen spectrum and b is the carbon spectrum. From the hydrogen spectrum, it can be seen that there are 9 H in 2-(4-bromophenyl)-1,3-dioxolane, with 4 different chemical environments. The d peaks of δ at 7.39 and 7.37 are 2 H close to Br on the benzene ring, J=8; the d peaks of δ at 7.23 and 7.21 are 2 H away from Br on the benzene ring, J=8; the s peak of δ at 5.62 is 1 H on the carbon connected to the benzene ring on the dioxolane; the d peaks of δ at 3.94 and 3.85 are 4 H away from the benzene ring on the dioxolane, J=36.

[0080] From the carbon spectrum, we can see that there are 9 Cs in 2-(4-bromophenyl)-1,3-dioxolane, and 6 different chemical environments. The peak at 136.02 is the C on the benzene ring connected to the dioxolane; the peak at 130.38 is the 2 Cs on the benzene ring close to Br; the peak at 121.17 is the 2 Cs on the benzene ring far from Br; the peak at 122.09 is the C on the benzene ring connected to Br; the peak at 101.87 is the C on the dioxolane connected to the benzene ring; the peak at 64.19 is the 2 Cs on the dioxolane far from the benzene ring.

[0081] Depend on Figure 1 It can be seen that the structural formula for synthesizing 2-(4-bromophenyl)-1,3-dioxolane is structure 5: Formula 5.

[0082] (2) The bis(4-(1,3-dioxolane-2-yl)phenyl)dimethylsilane prepared in Example 1 was subjected to H-NMR and C-NMR tests, respectively. The results are as follows: Figure 2As shown, a is the hydrogen spectrum and b is the carbon spectrum. From the hydrogen spectrum, it can be seen that there are 24 H in bis(4-(1,3-dioxolan-2-yl)phenyl)dimethylsilane, with 5 different chemical environments. The d peaks at 7.46 and 7.44 of δ are 4 H close to Si on the benzene ring, J=8; the d peaks at 7.38 and 7.36 of δ are 4 H away from Si on the benzene ring, J=8; the s peak at 5.74 of δ is 2 H on the carbon connected to the benzene ring on the dioxolane ring; the d peaks at 4.04 and 3.95 of δ are 8 H away from the benzene ring on the dioxolane ring, J=36; the s peak at 0.46 of δ is 6 H on the methyl connected to Si.

[0083] From the carbon spectrum, it can be seen that there are 20 Cs in bis(4-(1,3-dioxolane-2-yl)phenyl)dimethylsilane, with 7 different chemical environments. The peak at δ141.66 is the 2 Cs connected to the dioxolane ring on the benzene ring; the peak at δ141.16 is the 2 Cs connected to Si on the benzene ring; the peak at δ136.70 is the 4 Cs close to Si on the benzene ring; the peak at δ128.13 is the 4 Cs far from Si on the benzene ring; the peak at δ106.05 is the 2 Cs connected to the dioxolane ring on the benzene ring; the peak at δ67.73 is the 4 Cs far from the benzene ring on the dioxolane ring; the peak at δ-0.23 is the 2 Cs of the methyl group connected to Si.

[0084] Depend on Figure 2 It can be seen that the structural formula of bis(4-(1,3-dioxolane-2-yl)phenyl)dimethylsilane is Formula 6: Formula 6.

[0085] (3) The 4,4'-(dimethylsilanediyl)benzaldehyde prepared in Example 1 was subjected to H-NMR and C-NMR tests, respectively. The results are as follows: Figure 3 As shown, a is the hydrogen spectrum and b is the carbon spectrum. From the hydrogen spectrum, it can be seen that there are 16 H in 4,4'-(dimethylsilanediyl)benzaldehyde, with 4 different chemical environments. The s peak at δ at 9.94 is the 2 H on the aldehyde group; the d peaks at δ at 7.78 and 7.76 are the 4 H on the benzene ring close to the aldehyde group, J=8; the d peaks at δ at 7.61 and 7.59 are the 2 H on the benzene ring close to Si, J=8; the s peak at δ at 0.56 is the 6 H on the methyl group connected to Si.

[0086] From the carbon spectrum, it can be seen that there are 16 Cs in 4,4'-(dimethylsilanediyl)benzaldehyde, with 6 different chemical environments. The peak at 191.42 is for the 2 Cs on the aldehyde group; the peak at 144.61 is for the 2 Cs on the benzene ring connected to Si; the peak at 135.87 is for the 2 Cs on the benzene ring connected to the aldehyde group; the peak at 133.63 is for the 4 Cs on the benzene ring close to Si; the peak at 127.79 is for the 4 Cs on the benzene ring close to the aldehyde group; the peak at -3.86 is for the 2 Cs on the methyl group connected to Si.

[0087] Depend on Figure 3 It can be seen that the structural formula of 4,4'-(dimethylsilanediyl)benzaldehyde is formula 7: Formula 7.

[0088] (4) XPS characterization of the dynamic two-dimensional organosilicon polymer prepared in Example 1 was performed. The results are as follows: Figures 4 to 7 As shown, Figure 4 is the XPS total spectrum, Figure 5 is the C 1s-XPS spectrum, Figure 6 is the N-XPS spectrum, Figure 7 This is the Si-XPS spectrum.

[0089] Figure 4 The XPS total spectrum shows four elements: C, N, Si and O. Among them, C, N and Si are the same as the elemental composition of the dynamic two-dimensional organic silicon polymer molecular structure, while O is mainly attributed to the oxygen adsorbed by the material.

[0090] Figure 5 The high-resolution C 1s spectrum was deconvoluted into four peaks at 284.6, 283.6, 286 and 287, which are respectively attributed to sp 2 C=C,sp 3 C-Si, sp 2 C=N and C=O bonds. And sp 2 C=C, sp 3 C-Si、sp 2 The abundance ratio of C=N is close to 6:1:1, which is consistent with the sp 2 C=C,sp 3 C-Si and sp 2 The theoretical ratio of C=N is consistent. In the high-resolution C 1s spectrum, the abundance of C=O bonds is high, which is due to the oxidation of terminal groups in addition to the amide bonds in 2D-COSi-Me.

[0091] Figure 6The N-XPS spectrum of 2D-COSi-Me was deconvoluted into two peaks at 398.7 and 397.5, which were respectively attributed to the C=N bond and the N≡N bond, which were consistent with the chemical structure of 2D-COSi-Me. The appearance of the N≡N peak may be due to the nitrogen adsorbed on the sample surface.

[0092] Figure 7 There is only one small peak at 102.7 in the Si-XPS spectrum of , which is attributed to the Si-C bond in the 2D-COSi-Me sample.

[0093] The above results show that the bonding environment of each element is close to the theoretical value, indicating that the synthesized product is the target designed substance with the structural formula of Formula 1-1.

[0094] The dynamic two-dimensional organosilicon polymers prepared in Examples 1 to 3 have the same structure, and the only difference is the yield.

[0095] (5) A series of characterizations were conducted by Fourier transform infrared spectroscopy (FT-IR) on the changes in functional groups during the synthesis of 4,4'-(dimethylsilanediyl)benzaldehyde, melamine, and the samples 2D-COSi-Me prepared in Example 1 and Example 2. The results are as follows: Figure 8 shown. Figure 8 Here, Si-COF vacuum represents the 2D-COSi-Me prepared in Example 2, Si-COF solvothermal represents the 2D-COSi-Me prepared in Example 1, and Si-COF precursor represents 4,4′-(dimethylsilanediyl)benzaldehyde. Figure 8 The results show that 2D-COSi-Me was prepared under vacuum and solvent hot pressure at 120°C. Infrared showed that 2D-COSi-Me had CH bond vibration (3010 cm -1 -3100 cm -1 ), NH bond vibration (1650 cm -1 、780 cm -1 )、C=C bond vibration(1550 cm -1 , 1450 cm -1 )、C=N bond vibration(1000 cm -1 ), CN bond vibration (1340 cm -1 , 1350 cm -1 ) and Si-C bond vibration (1100 cm -1 ). By comparing the infrared data of the precursor 4,4'-(dimethylsilanediyl)benzaldehyde (referred to as Si COF precursor) and melamine, it was initially found that the crude product 2D-COSi-Me contained unreacted melamine, which needed to be removed by solvent extraction.

[0096] (6) The thermal stability of melamine was tested by thermogravimetric analysis (TGA). The results are as follows: Fig. 9 As shown. In the test range of room temperature 25℃ to 800℃, melamine showed two stages of mass loss. The first stage of mass loss occurred at 132℃, which was analyzed as the volatilization of the solvent attached to melamine. The second stage of mass loss occurred at 320℃, indicating that melamine underwent thermal decomposition and quickly decomposed completely, losing all its mass.

[0097] The thermal stability of 2D-COSi-Me prepared in Example 1 was further tested by thermogravimetric analysis (TGA). Fig.10 As shown. In the test range of 25℃ to 800℃, the 2D-COSi-Me sample showed three stages of mass loss. Among them, the first mass loss occurred at 80℃, which was analyzed as the volatilization of the solvent attached to 2D-COSi-Me. The second mass loss occurred at 399℃. By comparing with the TGA data of melamine, the mass loss at this position was mainly attributed to the decomposition of melamine and oligomers encapsulated in 2D-COSi-Me, and the mass loss after that was the thermal decomposition of 2D-COSi-Me, and all the mass was lost at 710℃, indicating that 2D-COSi-Me will completely decompose above 700℃.

[0098] (7) The 2D-COSi-Me sample prepared in Example 1 was observed under an optical microscope. The results are as follows: Fig.11 As shown. Fig.11 It can be seen that the 2D-COSi-Me samples are rhombus-shaped with different sizes ranging from 20 to 600 μm.

[0099] Under transmission electron microscopy (TEM), the rhombohedral morphology of 2D-COSi-Me was also observed (e.g. Fig.12 In (a) and (b)), and under high-resolution electron microscopy (HRTEM), lattice fringes with a length of 0.42 nm were observed (e.g. Fig.12 (c) and (d)).

[0100] Application Examples Electrolyte membrane preparation process: 6 mg of 2D-COSi-Me prepared in Example 1 and 10 mL of acetonitrile were added to a 20 mL glass bottle and stirred for 24 h. 600 mg of PEO (polyethylene oxide) and 219 mg of LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) were then added and stirred for 24 h to obtain an electrolyte slurry (eg Fig.13 5 mL of electrolyte slurry was taken with a pipette and evenly applied to the PTFE mold. After standing for 2 h, it was vacuum dried at 50 °C for 12 h. The film was peeled off from the mold and cut into a 2 cm diameter circular diaphragm (as shown in Fig.14 The electrolyte membrane doped with 1% 2D-COSi-Me was obtained. The lithium foil was cut into 1 cm diameter discs, and the battery was assembled in the order of positive electrode shell, lithium foil, separator, lithium foil, steel sheet, shrapnel, and negative electrode shell.

[0101] Preparation of pure PEO electrolyte membrane: Same as above, except that 2D-COSi-Me is not added.

[0102] Preparation of electrolyte membrane doped with 2% 2D-COSi-Me: Same as above, except that the mass of 2D-COSi-Me is 12 mg.

[0103] The SEM observation of PEO electrolyte membrane and its interface morphology showed that Fig.15 The SEM image of PEO doped with 2% 2D-COSi-Me is shown in Fig.16 shown.

[0104] Depend on Fig.15 and Fig.16 It can be seen that compared with the pure PEO electrolyte membrane, the PEO electrolyte membrane with 2% 2D-COSi-Me is smoother. No obvious phase separation phenomenon is observed. This shows that the added 2D-COSi-Me has a similar effect as an adhesive, making the entire electrolyte membrane more complete, which is beneficial to the contact between the electrolyte and the electrode material, thereby improving the battery performance.

[0105] Elemental analysis was performed at different locations of the PEO electrolyte membrane doped with 2% 2D-COSi-Me. The results are as follows: Fig.17 shown. Fig.17 It shows that the content of Si element does not change much, indicating that 2D-COSi-Me is uniformly incorporated into PEO.

[0106] Comparison of battery cycle stability The electrochemical test was carried out using a 2032-type button cell. After doping with 1% 2D-COSi-Me, the cycle stability test was carried out at 60°C. The results are shown in Fig.18 As shown, Fig.18 In the figure, a and c are the PEO electrolyte membrane at 0.1 mA·cm -2 、0.1mAh·cm -2 and 0.2 mA·cm -2 , 0.2mAh·cm -2 Cyclic stability test results under the following conditions: (a) and (d) are the electrolyte membrane formed after doping with 1% 2D-COSi-Me at 0.1 mA·cm -2 、0.1mAh·cm -2 and 0.2 mA·cm -2 , 0.2mAh·cm-2 Cyclic stability test results under 400 nm conditions. Fig.18 Display, at 0.1 mA cm -2 , 0.1mAh·cm -2 (Indicates that the current density is 0.1 mA cm -2 , capacity density is 0.1mA·cm -2 ) and 0.2 mA·cm -2 , 0.2mAh·cm -2 Under these conditions, the PEO electrolyte membrane can only operate stably for about 100 h and 60 h respectively, and its failure is manifested as a short circuit in the battery. However, after adding 2D-COSi-Me, the battery can operate stably at 0.1 mA·cm -2 , 0.1mAh·cm -2 and 0.2 mA·cm -2 , 0.2mAh·cm -2 Under the same conditions, it can run stably for more than 300h and 230h respectively, which shows that its stability is better than that of PEO electrolyte membrane.

[0107] At 60°C, 0.1 mA cm -2 , 0.1mAh·cm -2 Under the conditions, the effect of the amount of addition on the stability of the electrolyte was observed. The results are as follows Fig.19 shown. Fig.19 It is shown that after doping with 1% 2D-COSi-Me, it can run stably for 300h (see Fig.19 After adding 1.5% 2D-COSi-Me, the system can run stably for 380 h (see Fig.19 b), after adding 2% 2D-COSi-Me, it can run stably for up to 500h (see Fig.19 In Figure c), the stable operation time is reduced to 340 h after adding 2.5% 2D-COSi-Me (see Fig.19 (d) This indicates that within a certain range, increasing the amount of 2D-COSi-Me can improve the electrolyte stability.

[0108] The variable temperature electronic impedance spectroscopy test was carried out in the range of 30~70℃. By analyzing the electron transfer resistance (R ct ) and temperature, using the Arrhenius formula (R: resistance; A: pre-exponential factor; E a : activation energy; R: gas constant; T: temperature) to calculate the activation energy of electron transfer. The result is as follows Fig. 20As shown in a. By comparison, after PEO was doped with 1% 2D-COSi-Me, the activation energy of electron transfer decreased from 0.370eV to 0.283eV. The reduced activation energy is further reflected in the change of conductivity. In the range of 30~70℃, after the addition of 1% 2D-COSi-Me, the conductivity of the electrolyte increased by 25~800% (see Fig. 20 (b) Higher conductivity is beneficial to the cycle stability of the battery and reduces the growth of lithium dendrites during the battery cycle.

[0109] In addition, the present invention also carried out mechanical tensile tests on the electrolyte membrane, and the results are shown in Fig.21 .from Fig.21 It can be seen that the fracture strength of pure PEO electrolyte membrane is 0.36MPa and the maximum strain is 786%. After adding 1% 2D-COSi-Me, its mechanical properties have been greatly improved, and its fracture strength and maximum strain have increased by about 1 times to 0.84MPa and 1561%. Better mechanical properties are also conducive to improving the cycle stability of the battery and increasing the battery life.

[0110] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A dynamic two-dimensional organosilicon polymer, characterized in that: The structural unit has the structure shown in Formula 1: Formula 1; In Formula 1, R is -CH3, -C2H5, -C3H7, -CH(CH3)2, -C6H6 or -O-[Si(CH3)2-O] n -CH3, n is an integer from 1 to 11.

2. The method for preparing the dynamic two-dimensional organosilicon polymer according to claim 1, characterized in that: The following steps are involved: (1) dissolving 2-(4-bromophenyl)-1,3-dioxolane in tetrahydrofuran and cooling to -60 to -95°C, adding an organic lithium reagent to carry out an intermediate reaction, adding a tetrahydrofuran solution of dichlorosilane to the obtained intermediate system and heating to room temperature to carry out a nucleophilic substitution reaction to obtain a compound with a structure shown in Formula 3; The dichlorosilane has a structure shown in Formula 2: Formula 2; Formula 3; In Formula 2 and Formula 3, R is -CH3, -C2H5, -C3H7, -CH(CH3)2, -C6H6 or -O-[Si(CH3)2-O] n -CH3, n is an integer from 1 to 11; (2) dissolving the compound of the structure represented by Formula 3 in acetone and mixing the mixture with water and a strong inorganic acid to carry out a deprotection reaction to obtain a compound of the structure represented by Formula 4; Formula 4; (3) The compound having the structure shown in Formula 4 is polymerized with melamine to obtain the dynamic two-dimensional organosilicon polymer.

3. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of 2-(4-bromophenyl)-1,3-dioxolane to dichlorosilane is (1-4):

1.

4. The preparation method according to claim 2 or 3, characterized in that: In step (1), the molar ratio of the 2-(4-bromophenyl)-1,3-dioxolane to the organic lithium reagent is 1:(0.5-1.5); The organic lithium reagent includes one or more of n-butyl lithium, sec-butyl lithium and tert-butyl lithium.

5. The preparation method according to claim 2, characterized in that: In step (2), the mass ratio of the compound of the structure represented by formula 3 to the volume ratio of water is 1 g: 8-12 mL.

6. The preparation method according to claim 2, characterized in that: In step (3), the polymerization reaction of the compound represented by formula 4 and melamine includes method 1 or method 2; The method 1 comprises the following steps: The compound of the structure shown in Formula 4 and melamine are dissolved in a mixed solvent, an organic weak acid catalyst is added to the obtained solution, and then the solution is vacuum-sealed and allowed to stand under vacuum-sealed conditions to perform a polymerization reaction; the mixed solvent is a combination of 1,4-dioxane and mesitylene, or a combination of n-butanol and o-dichlorobenzene; The second method comprises the following steps: The compound with the structure shown in Formula 4 and melamine are dissolved in a high boiling point solvent, an organic weak acid catalyst is added to the obtained solution, and a polymerization reaction is carried out in an inert atmosphere or a vacuum atmosphere under static conditions; the high boiling point solvent includes one or more of dimethyl sulfoxide, chlorobenzene, dichlorobenzene and N,N-dimethylformamide.

7. The preparation method according to claim 6, characterized in that: When the polymerization reaction is carried out using method 1 or method 2, the molar ratio of the compound with the structure represented by formula 4 to melamine is 3:(1.8-2.2).

8. The preparation method according to claim 6 or 7, characterized in that: When the polymerization reaction is carried out by method 1, the polymerization reaction temperature is 60-80° C. and the time is 60-80 hours; When the polymerization reaction is carried out using method 2, the polymerization reaction temperature is 110-130° C. and the time is 60-80 hours.

9. Use of the dynamic two-dimensional organosilicon polymer according to claim 1 or the dynamic two-dimensional organosilicon polymer prepared by the preparation method according to any one of claims 2 to 8 in an electrolyte membrane.

10. The use according to claim 9, characterized in that: The electrolyte membrane comprises a matrix, an electrolyte salt and a dynamic two-dimensional organic silicon polymer, wherein the mass of the dynamic two-dimensional organic silicon polymer is 1-5% of the mass of the matrix.

Citation Information

Patent Citations

  • Covalent organic framework compound with side chain modified with phosphoric acid as well as preparation method and application of covalent organic framework compound

    CN113372563A

  • Benzofuryl covalent organic framework material as well as preparation method and application thereof

    CN117186332A

  • Nitrogen-doped and carbon matrix-encapsulated silicon-carbon nanofiber composite, method for preparing same, and secondary battery comprising same

    WO2023239046A1